2013
DOI: 10.1111/os.12047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Blood HbA1c Level on Surgical Treatment Outcomes of Diabetics with Ankle Fractures

Abstract: Blood HbA1c levels appear to be predictive of risk and complication rates in the surgical treatment outcomes of diabetic patients with ankle fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 23 publications
(26 reference statements)
0
33
0
Order By: Relevance
“…Liu et al found that HbA1c > 6.5% was associated with increased rates of poor radiological outcomes, revisions, and complications in ankle surgery. (10) M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al found that HbA1c > 6.5% was associated with increased rates of poor radiological outcomes, revisions, and complications in ankle surgery. (10) M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…(9,10,(19)(20)(21)(22) However, it is unclear if the findings in cardiac and orthopedic surgery patients are generalizable to general surgery patients undergoing intraabdominal procedures. A recent single-institution study reported an association between HbA1c greater than 8% and increased length of stay.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The most significant complication in diabetic patients with ankle fractures is the risk of superficial and deep wound infections. In diabetic patients with ankle fractures, elevated HbA1C levels greater than 6.5% appear to be predictive of higher complication rates in those receiving surgical treatment [1]. This also establishes the importance of tight blood glucose control preoperatively and postoperatively.…”
mentioning
confidence: 74%
“…If syndesmosis injuries are present, percutaneous methods may also be used for fixation. Again, this allows for the least amount of incision with the greatest amount of stability [1].…”
mentioning
confidence: 99%